Latent vestibular dysfunction and its effect on quality of life in elderly individuals, the need of active screening and intervention - Swami, Himanshu; B. M., Aravind (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Dizziness is a commonly reported complaint among elderly.. Among the elderly in particular, factors such as Ageing, presbycusis, diabetes, chronic kidney disease, osteopenia, and osteoporosis increase the risk. Dizziness handicap inventory is used to assess the quality of life among the individuals with vestibular dysfunction. This is also used to assess the impact of interventions for vestibular dysfunction. This study aims to estimate the prevalence of latent vestibular dysfunction among the Indian population, and the impact of interventions among the same. Methods: A prospective observational study was conducted at a tertiary care hospital. As per sample size estimates, 200 participants aged >60 years without previous diagnosis of vestibular dysfunction were screened using appropriate tests. The quality of life of the affected individuals were assessed using Dizziness Handicap Inventory Score (DHIS) before and after intervention. Results: The prevalence of latent vestibular dysfunction was found to be 23.5%. Most of them reported having moderate handicap due to the condition. Following intervention, those with moderate handicap either became normal (47.8%) or had residual mild handicap (52.2%). The mean DHIS score significantly decreased from 40.91 points during pre-intervention to 16.12 points post-intervention. Conclusions: Around one-fourth of the Indian elderly is found to have latent vestibular dysfunction. It has a major impact on the individual’s quality of life. Yet, screening and intervention is found to make a considerable improvement among the affected individuals.